The Impact of Gamified Therapy on Physical, Cognitive, & Emotional Outcomes in Children with Cerebral Palsy: A Case Study Analysis - Tommy, Robin; Badrinarayanan, M.K.; George, Smitha Rosemary; Ravindranathan, Reshmi (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: Cerebral palsy (CP) is a neurological disorder affecting motor, cognitive, and social development in children. Traditional therapies often struggle with engagement and adherence. This study evaluates a novel gamified treatment developed with the SHIFT Framework to improve outcomes in children with CP. Methods: A case study design assessed the effects of gamified therapy on seven children with various types and severities of CP. The intervention used the SHIFT Framework to include engaging game elements and customizable features. Assessments before and after the intervention measured hand-eye coordination, balance, motor skills, cognitive engagement, motivation, and emotional well-being using appropriate statistical methods. Results: Post-intervention, all cases showed improved motor skills, coordination, balance, cognitive engagement, and emotional states. Increased levels of attention, motivation, and persistence were noted, alongside enhanced therapy engagement. Statistical analysis revealed significant improvements (p<0.05) in most parameters. Conclusion: The gamified therapy approach using the SHIFT Framework effectively enhanced physical, cognitive, and emotional outcomes for children with CP. The engaging, personalized intervention improved motivation, adherence, and functional outcomes, particularly in cognitive aspects relevant to intellectual disabilities associated with CP. Further studies with larger cohorts and extended follow-ups are necessary to confirm these results and expand on the therapy’s applicability in CP management.